الرقابة القضائية عمى أعمال الييئات التنفيذية لمجماعات المحمية - صثتي ،كمال (جامعة الوادي University of El Oued, 2025)
تُعتبر الرقابة القضائية من أهم الضمانات التي أقرها المشرع الجزائري، والتي يتمتع بها الأفراد في تعاملهم مع الإدارة عمومًا، ومع قرارات وأعمال الأجهزة التنفيذية للجماعات المحلية خصوصًا، في تعاملها مع المواطنين. وتتخذ هذه الإجراءات شكلين: القرارات الإدارية والعقود (العقود العمومية). ولإيجاد توازن بين امتيازات السلطة العامة وحقوق الأفراد، منح المشرع الأفراد سلطة رفع الدعاوى القضائية ضد القرارات والأعمال غير القانونية، وضد العقود العمومية الصادرة عن الوالي، بصفته الجهاز التنفيذي للدولة، أو رئيس المجلس الشعبي البلدي، بصفته الجهاز التنفيذي للبلدية. وذلك لحماية الحقوق والحريات، وضمان مبدأ المشروعية، ومنع إساءة استعمال السلطة. Judicial oversight is considered one of the most important guarantees established by the Algerian legislature, which individuals possess when dealing with the administration in general, and with the decisions and actions of the executive bodies of local authorities in particular, in their dealings with citizens. These actions take two forms: administrative decisions and contracts (public contracts). In order to create a balance between the privileges of public authority and the rights of individuals, the legislature has granted individuals the authority to file lawsuits against unlawful decisions and actions, and against public contracts issued by the governor, in his capacity as the executive body of the state, or the president of the municipal people's council, in his capacity as the executive body of the municipality. This is to protect rights and freedoms, ensure the principle of legality, and prevent the abuse of power.
قانون إداري
Keywords: الرقابة القضائية ، أعمال الهيئات ،التنفيذية ،للجماعات المحلية; Judicial oversight of the work of executive bodies and local authorities.